2021
DOI: 10.1002/asia.202100838
|View full text |Cite
|
Sign up to set email alerts
|

2D Silicate Materials for Composite Polymer Electrolytes

Abstract: Two-dimensional (2D) silicate materials have become one of the promising candidates for constructing composite polymer electrolytes due to their advantages of low cost, high stability, good mechanical property, high ionic conductivity and potential to inhibit the growth of lithium dendrites. However, the application of 2D silicate materials in composite polymer electrolytes (CPEs) is still at the infancy stage and facing a lot of challenges. In this minireview, we summarize the structures and properties of 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…Compared with other clay minerals, MMT has been applied more wildly in EES devices due to the following features: (1) it is an efficient ionic conductor of various ions, e.g., H + , Li + , Na + , Zn 2+ , Mg 2+ , and so forth; 8,[14][15][16] (2) it has an ordered 2D laminar nanostructure with terrific chemical/thermal/mechanical stability, high hydrophilicity, high ion exchange capability, and excellent adsorption performance; 1,6,[17][18][19] (3) it has a tuneable pore structure, ion transport channel structure, and specific surface area. 1,20,21 However, the practical applications of MMT in EES devices are still hampered by several crucial shortcomings of MMT, especially its intrinsically low electronic conductivity and poor electrocatalytic activity. 21,22 Moreover, as an electrochemically inert component, the introduction of MMT will lead to the loss of energy densities of the EES devices.…”
Section: Xin Hementioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other clay minerals, MMT has been applied more wildly in EES devices due to the following features: (1) it is an efficient ionic conductor of various ions, e.g., H + , Li + , Na + , Zn 2+ , Mg 2+ , and so forth; 8,[14][15][16] (2) it has an ordered 2D laminar nanostructure with terrific chemical/thermal/mechanical stability, high hydrophilicity, high ion exchange capability, and excellent adsorption performance; 1,6,[17][18][19] (3) it has a tuneable pore structure, ion transport channel structure, and specific surface area. 1,20,21 However, the practical applications of MMT in EES devices are still hampered by several crucial shortcomings of MMT, especially its intrinsically low electronic conductivity and poor electrocatalytic activity. 21,22 Moreover, as an electrochemically inert component, the introduction of MMT will lead to the loss of energy densities of the EES devices.…”
Section: Xin Hementioning
confidence: 99%
“…A few reviews have generally reported the research progress of clays in the energy conversion and storage field. 1,6,20 However, the application of MMT in the EES field has not been specifically and comprehensively reviewed. Recently, many new research studies on the design, preparation, application, and mechanism investigation of MMT-based materials in EES devices have been reported and the latest progress and achievements need to be thoroughly and deeply summarized.…”
Section: Kelei Huangmentioning
confidence: 99%
“…Silica is also widely used as a reinforcement in some composite materials such as: agricultural waste composites and foliage [8][9][10], composite mortar and concrete [11,12], and also as a filler material in some electrolyte [13][14][15]. The addition of silica to the composite can improve the interaction between polymer particles, thereby increasing the strength of the composite and can improve its mechanical properties [7,14,15]. The use of PU and quartz sand which has a high silica component is expected to be used as raw material for construction materials such as concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-organic batteries (LOBs) stand out among advanced battery technologies for their high reversible capacity, good resource sustainability, and low environmental impact. However, their practical applications have been hampered by a serious technology obstacle of high dissolution of organic active materials, especially for small-molecule quinones, which eventually results in fast capacity decay and low Coulombic efficiency. Among the considerable efforts to conquer this problem, the introduction of a permselective membrane between electrodes is intriguing . The separators endowed with abundant negative charge or unique size effects against organic redox intermediates can mitigate the shuttling effect, resulting in a long cycle life. For example, a Li-IDAQ battery with a Nafion-based sandwich-type separator displayed a long-term cycling stability (262 mAh g –1 for the initial value) with a capacity retention of 76% after 400 cycles . Kang’s group recently developed a ZIF-8 MOF-based gel separator for LOBs .…”
Section: Introductionmentioning
confidence: 99%